Moral hazard and ambiguity - Philipp Weinschenk (Max Planck Institute for Research on Collective Goods, 2010)
We consider a principal-agent model with moral hazard where the agent's knowledge about the performance measure is ambiguous and he is averse towards ambiguity. We show that the principal may optimally provide no incentives or contract only on a subset of all informative performance measures. That is, the Informativeness Principle does not hold in our model. These results stand in stark contrast to the ones of the orthodox theory, but are empirically of high relevance.
Keywords: D82; M12; M52; 330; Moral Hazard; Ambiguity Aversion; Principal-Agent Model; Informativeness Principle; Moral Hazard; Risikoaversion; Prinzipal-Agent-Theorie; Leistungsbeurteilung; Informationswert; Theorie